2022
DOI: 10.3390/curroncol29020052
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Prognosis Analysis of Younger Bladder Cancer Patients

Abstract: Background: Generally, little is known about prognostic factors in bladder cancer patients under 40 years of age. We therefore performed a retrospective study to identify prognostic factors in these younger bladder cancer patients. Methods: We collected clinicopathological data on bladder cancer patients ≤40 years old diagnosed between 1975 and 2018 from the Surveillance, Epidemiology, and End Results (SEER) database. Survival curves were generated using the Kaplan–Meier method, and the differences between gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…In light of these results, we caution against the excessive use of radiotherapy in UCB patients. Furthermore, our nomogram underscored the detrimental prognosis linked to larger tumor sizes in UCB cases, a nding echoed in various studies (33).…”
Section: Discussionsupporting
confidence: 69%
“…In light of these results, we caution against the excessive use of radiotherapy in UCB patients. Furthermore, our nomogram underscored the detrimental prognosis linked to larger tumor sizes in UCB cases, a nding echoed in various studies (33).…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, the nomogram also illustrated that an increase in cancer size resulted in a poorer prognosis in bladder cancer patients. Other studies have further confirmed the influence of cancer size on bladder cancer-specific prognosis [ 30 ]. Moreover, the number of cancers is also related to the prognosis of bladder cancer.…”
Section: Discussionmentioning
confidence: 74%
“…The primary tumor distinguishability on PET and CT was associated with mortality in patients with BC in univariate analysis. It is known that the size of the primary tumor in BC is a prognostic factor ( 20 , 21 ). Patients with larger primary tumors might have more distinguishable tumors on PET and/or CT; therefore, their prognosis might be poorer than others.…”
Section: Discussionmentioning
confidence: 99%